(untitled) (Semiárida, 2020)
This research was conducted in a Larrea divaricata’s shrubland with short grasses in the Southeast of La Pampa. It was determined standing crop cover and frequency of all grasses and forbs four times a year. Aerial phytomass reached 19, 62, 177 and 144 gDM/m2 in May, August, November/82 and March/83. Piptochaetium napostaense y Stipa tenuis, two dominant species had more than 80% of frequency. Vegetation’s cover ranged 60-70% whereas bare soil had a 5 - 9% range.